EIF5A2 enhances stemness of epithelial ovarian cancer cells via a E2F1/KLF4 axis - Kun Wang; Yiyang Wang; Yuanjian Wang; Shujie Liu; Chunyan Wang; Shuo Zhang; Tianli Zhang; Xingsheng Yang (Stem Cell Research & Therapy, 2021)
Abstract Background Ovarian cancer stem cells (OCSC), endowed with tumor-initiating and self-renewal capacity, would account not only for the tumor growth, the peritoneal metastasis, and the relapse, but also for the acquisition of chemotherapy resistance. Nevertheless, figuring out their phenotypical and functional traits has proven quite challenging, mainly because of the heterogeneity of ovarian cancer. A deeper understanding of OCSC mechanisms will shed light on the development of the disease. Therefore, we aim to explore it for the design of innovative treatment regimens which aim at the eradication of ovarian cancer through the elimination of the CSC component. Methods In this study, immunohistochemistry assay and western blot assay were used to detect protein expression in the primary tumor and peritoneal multi-cellular aggregates/spheroids (MCAs/MCSs). OCSCs induced from cell line SKOV3 and HO-8910 were enriched in a serum-free medium (SFM). The effect of EIF5A2 on CSC-like properties was detected by sphere-forming assays, re-differentiation assays, quantitative real-time polymerase chain reaction, western blotting, flow cytometry, cell viability assays, immunofluorescence staining, and in vivo xenograft experiments. RNA-sequencing (RNA-seq) was used to reveal the mechanism by which EIF5A2 positively modulates the stem-like properties of ovarian cancer cells. Results Expression of EIF5A2 was significantly higher in peritoneal MCAs/MCSs compared to matched primary tumors, and EIF5A2 was also unregulated in ovarian cancer cell line-derived spheroids. Knockdown of EIF5A2 reduced the expression of the stem-related markers (ALDH1A1 and OCT-4), inhibited self-renewal ability, improved the sensitivity to chemotherapeutic drugs, and inhibited tumorigenesis in vivo. Mechanistic studies revealed that EIF5A2 knockdown reduced the expression of KLF4, which could partially rescue stem-like properties abolished by EIF5A2 knockdown or strengthened by EIF5A2 overexpression, through the transcription factor E2F1, which directly bind to KLF4 promoter. Conclusion Our results imply that EIF5A2 positively regulates stemness in ovarian cancer cells via E2F1/KLF4 pathway and may serve as a potential target in CSCs-targeted therapy for ovarian cancer.